Muwathanah Education in Maqasyid Perspective - Inayatillah; Kamaruddin (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
The concept of muwathanah education in Islam is actually how to instill nationalism values followed by serious efforts in building the country according to their respective sciences and fields. In fact, there is still muwathanah education that deliberately transfers the values of hatred towards the state even the most extreme want to change the ideology of the state. The gap is the author's attraction to explain how the position of muwathanah education in the view of maqashid. This article is classified as literature research with a qualitative approach. The methodology used is a descriptive analysis study and a comparative study. The results of the study concluded; First, muwathanah education is permissible, but it can be turned into compulsory and sunnah as long as it remains within the 5 essences of maqashid. Conversely, it can become haram (forbidden) if the education seeks to breed hatred and damage to the state. Second, loyalty to the state in classical Islam was evidenced by taking a bayat (oath of allegiance) to the Prophet as leader. In modern times, loyalty to the Indonesian state is carried out by recognizing Pancasila and Constitution of 1945 as a mutual agreement.